(untitled) (Scientific journal of the Fergana State University, 2024)
This article highlights similar and different aspects of communicative-pragmatic intentions in commercial correspondence. According to the author, intentional characters are a text-forming factor. Based on the research of various linguists, the article emphasizes that the main purpose of business correspondence is to manage the relationship between the parties involved in formal communication and to provide information on an issue in a specific situation.